Generation and miRNA Characterization of Equine Induced Pluripotent Stem Cells Derived from Fetal and Adult Multipotent Tissues. (2nd May 2019) - Pessôa, Laís Vicari de Figueiredo; Pires, Pedro Ratto Lisboa; del Collado, Maite; Pieri, Naira Caroline Godoy; Recchia, Kaiana; Souza, Aline Fernanda; Perecin, Felipe; da Silveira, Juliano Coelho; de Andrade, André Furugen Cesar; Ambrosio, Carlos Eduardo; Bressan, Fabiana Fernandes; Meirelles, Flavio Vieira
Abstract : Introduction . Pluripotent stem cells are believed to have greater clinical potential than mesenchymal stem cells due to their ability to differentiate into almost any cell type of an organism, and since 2006, the generation of patient-specific induced pluripotent stem cells (iPSCs) has become possible in multiple species. Objectives . We hypothesize that different cell types respond differently to the reprogramming process; thus, the goals of this study were to isolate and characterize equine adult and fetal cells and induce these cells to pluripotency for future regenerative and translational purposes. Methods . Adult equine fibroblasts (eFibros) and mesenchymal cells derived from the bone marrow (eBMmsc), adipose tissue (eADmsc), and umbilical cord tissue (eUCmsc) were isolated, their multipotency was characterized, and the cells were induced in vitro into pluripotency (eiPSCs). eiPSCs were generated through a lentiviral system using the factors OCT4, SOX2, c-MYC, and KLF4. The morphology and in vitro pluripotency maintenance potential (alkaline phosphatase detection, embryoid body formation, in vitro spontaneous differentiation, and expression of pluripotency markers) of the eiPSCs were characterized. Additionally, a miRNA profile analysis of the mesenchymal and eiPSCs was performed. Results . Multipotent cells were successfully isolated, but the eBMmsc failed to generate eiPSCs. The eADmsc-, eUCmsc-, and eFibros-derived iPSCs were positive for alkaline phosphatase, OCT4 and NANOG, were exclusively dependent on bFGF, and formed embryoid bodies. The miRNA profile revealed a segregated pattern between the eiPSCs and multipotent controls: the levels of miR-302/367 and the miR-92 family were increased in the eiPSCs, while the levels of miR-23, miR-27, and miR-30, as well as the let-7 family were increased in the nonpluripotent cells. Conclusions . We were able to generate bFGF-dependent iPSCs from eADmsc, eUCmsc, and eFibros with human OSKM, and the miRNA profile revealed that clonal lines may respond differently to the reprogramming process.